Empathic accuracy in design: Exploring design outcomes through empathic performance and physiology. (2020) - Chang-Arana, Álvaro M.; Piispanen, Matias; Himberg, Tommi; Surma-aho, Antti; Alho, Jussi; Sams, Mikko; Hölttä-Otto, Katja
Abstract : Empathic design highlights the relevance of understanding users and their circumstances in order to obtain good design outcomes. However, theory-based quantitative methods, which can be used to test user understanding, are hard to find in the design science literature. Here, we introduce a validated method used in social psychological research – the empathic accuracy method – into design to explore how well two designers perform in a design task and whether the designers' empathic accuracy performance and the physiological synchrony between the two designers and a group of users can predict the designers' success in two design tasks. The designers could correctly identify approximately 50% of the users' reported mental content. We did not find a significant correlation between the designers' empathic accuracy and their (1) performance in design tasks and (2) physiological synchrony with users. Nevertheless, the empathic accuracy method is promising in its attempts to quantify the effect of empathy in design.